Estetika gledališča za najmlajše - Šinko, Sabina (Revija za elementarno izobraževanje, 2011)
The Aesthetics of Theatre for Very Young Children. The article defines specifications of theatre for very young children. The main goal of this type of theatre is to give children younger than four the possibility of experiencing theatre. This type of performance, for this age group, can also be used in nursery education, psychology and art therapy. In this context artists try to find the right balance to make the theatre performance an experience and event for children without reducing the artistic value. The fact is that this type of theatre, in some aspects, has its own specifications that correspond to conventional theatre only. This article presents the experiencing of theatre performance for very young learners on the emotional level, discusses cognitive conditions of experiencing a performance, defines the role of actors and communicating through a play. The article also defines perceiving a play, the importance of space, speech, story, dramaturgy and time. The importance of children and parents sharing a theatre experience is described at the end. According to the completed research work in this field in Europe, this type of theatre contributes to the cognitive and emotional enrichment of children, their perception at all sensual levels and the development of speaking skills. It is also an important addition to aesthetic education practice in the preschool period.
Keywords: theatre for children; aesthetic education; aesthetic experience and perception of child; dramaturgic elements of theatre for young children